Juventude, juventudes: construção da política municipal para jovens de São Lourenço - MG - Soares, Renata (2012)
This paper aims to examine the understanding of the concept of youth, nowadays. Along with this search, we face the rise of public policies for this part of society, finally understood as complex, plural, able and willing to be a protagonist of its own story. Looking carefully, we wonder how to characterize the plurality of the youth of São Lourenço (MG). Can a municipal youth policy attend this plurality? Is the construction of such a policy appropriate to the plurality of youth? For this research, we believe that case study, as well as autobiographical research, would be the most appropriate methods for understanding this complex and deep reality. The basic theoretical concept was chosen from most recent studies on youth; theorists such as Castro and Aquino were very present in this work, as well as Sposito, Abramo, parents and Marías, in the first chapter. In the second chapter, in addition to the consistent contribution of Ninis and Giolito, the resources are some authors, local documents and electronic publications and my own personal background in the city. In the third chapter, my personal background, my work as an employee of the São Lourenço City Hall and my dissertation meet each other. Gilberto Velho shows us how memory, project and identity are significant in the personal life and the possibility of social transformation.(AU)